Rebound Effects of Exchange Rate and Central Bank Interventions in Selected ECOWAS Countries - Mustapha A. Akinkunmi (International Journal of Economics and Financial Issues, 2017)
This study examines the exchange rate rebound effects of the Central Bank intervention in the selected ECOWAS economies. An empirical understanding of these effects is very important to trade adjustment as well as the macroeconomic stability in these countries. Using the panel data modelling framework, the study finds that the impact of the Central Bank intervention on exchange rate is insignificant and it does not lead to the exchange rate rebound effect. In addition, monetary policy rate implemented by the monetary authorities significantly influences the level of exchange rate in a positive direction.